2020
DOI: 10.2298/jas2002137k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen levels and weed management methods on weed abundance and yield of upland rice (Oryza sativa L.)

Abstract: Weed infestation and inherent low soil fertility are among the major factors attributed to the low yield of rice in Nigeria. Field trials were therefore conducted to evaluate the effect of nitrogen application levels and weed control methods on growth and yield of upland rice (var. NERICA 2) at the Teaching and Research Farm of the Federal University of Agriculture, Abeokuta (07o 15?N, 03o 25?E) during 2015 and 2016 cropping seasons. Three nitrogen (N) levels (0, 60 and 90 kg/ha) were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…From the perspective of crop protection, it is necessary to study reasonable measures to eliminate Indian jointvetch from paddy fields. The advantages of chemical methods for weed control in upland direct-seeding rice fields have been reported for decades in terms of higher yields and lower labor costs [ 30 – 32 ]. However, the chemical control of Indian jointvetch is currently very challenging [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of crop protection, it is necessary to study reasonable measures to eliminate Indian jointvetch from paddy fields. The advantages of chemical methods for weed control in upland direct-seeding rice fields have been reported for decades in terms of higher yields and lower labor costs [ 30 – 32 ]. However, the chemical control of Indian jointvetch is currently very challenging [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current weed control methods in upland direct-seeding rice fields mainly include cultural weed management practices and physical methods such as deep plowing, germination, mechanical weeding, and hand-pulling weeding, along with chemical methods using herbicides [ 28 – 30 ]. Chemical methods for weed control in upland direct-seeding rice fields have specific advantages of obtaining higher yields with relatively lower labor costs [ 30 – 32 ]. Aeschynomene weeds are often controlled using a combination of imazapyr and imazapic herbicides [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…for the proper management of weeds, water and soil (Silva et al, 2007;Rodenburg and Johnson, 2009). The effect of timely fertiliser application (Adigun et al, 2017;Kolo et al, 2020), narrow row spacing (Kasim et al, 2017) and optimum seed rate (Ampong-Nyarko and De Datta, 1991;Johnson, 1996) to suppress weeds have been reported in rice systems in Africa. Apart from grain yield increase, Kasim et al (2017) reported that 14 cm row spacing was more effective in reducing weed density and biomass than 20 cm row spacing in upland rice.…”
Section: Cultural Weed Controlmentioning
confidence: 99%
“…Of all the factors attributed for the low yield of rice, weed competition is one of the most deleterious resulting in about 48 to 100% yield reduction (Adeyemi et al, 2017;Adigun et al, 2017;Kolo et al, 2020). On a global scale, 37% of the rice yield is considered to be lost to weeds (Oerke and Dehne, 2004).…”
Section: Introductionmentioning
confidence: 99%